Erwerbs- und Einkommenschancen im Kontext der intergenerationellen Einkommenspersistenz - Michael Mesch (Wirtschaft und Gesellschaft (WuG), 2016)
Empirical studies provide evidence that in Austria, compared to other EU-countries, intergenerational educational persistence is intermediate and intergenerational income persistence is high. Wealth, wealth transfers and educational homogamy have all been factors supporting persistence of income between generations. The first section of this paper is an overview of these empirical studies and sketches theoretical foundations. The empirical section investigates labour market conditions, such as unemployment rates, participation rates etc., and their respective developments by skill groups in Austria. It is shown that labour market conditions and developments have been contributing to intergenerational income persistence.
Keywords: 330; Österreich; Berufliche Qualifikation; Einkommen